SYNTHESIS METHOD OF OPTIMUM RECEIVABLE CHANNEL OF LITERAL APPARATUS MANAGEMENT - Мишуков, О. М.; Луценко, А. С.; Цураніч, В. В.; Шаповалов, В. С.; Радченко, В. М. (Science-based technologies, 2019)
The paper shows that at the stage of flight control of aircraft, a significant role is played by the investigation of their tactical and technical characteristics of control systems. The main way of ensuring high accuracy of flight control is to construct their receiving channels in an optimal way. Synthesis of characteristics of the receiving channel of the control system of aircraft by the partial quality index, in particular, the minimum of the average quadratic error of measurement of navigational parameters of motion, is possible if the task of restoration of the law of motion is reduced to the task of reproducing one or more parameters of this law, which remain unchanged in time measurement. It is substantiated that the law of motion of aircraft can be reasonably approximated by a polynomial with sufficient accuracy. The purpose of the work is to develop a method for synthesizing the optimal receiving channel of the aircraft management system. The proposed structural scheme of the instrument of the parameters of the aircraft. The construction of measuring channels by the proposed method enables to provide the best (highest) characteristics of accuracy. Such measuring devices should be used at small intervals of observation. It is noted that the main application side for implementation of the synthesized filtration system is contained in the development and practical implementation of digital microprocessor devices: discriminators, precision blocks, filters, units for evaluating the overall accuracy of filtration. It has been shown that in existing airborne control systems, the channels are mainly based on quasi-optimal circuits. Consequently, such systems can be upgraded in such a way as to optimize their accuracy. To this end, it is proposed to use the proposed method for synthesizing the optimal receiver of the control and control system of aircraft.